759 Development of an implantable artificial lymph node as a therapeutic cancer vaccine. (9th November 2020) - Viswanath, Dixita; Liu, Hsuan-Chen; Xuan Chua, Corrine Ying; Grattoni, Alessandro
Abstract : Background: Personalized therapeutic cancer vaccines aim to target and reprogram the host immune system to achieve cancer eradication in situ. Cancer vaccines deliver two main components: immunostimulants (iS) and tumor antigens to reduce tumor burden with a robust T cell response; however, none have reached broad clinical success due to difficulty in vaccine administration, ex vivo cellular manipulation, low clinical efficacy and broad administrative barriers. While most efforts to date have focused on repeated bolus administrations, biomaterial-based vaccine strategies have led to promising clinical translation. Methods: In light of these challenges, we have designed a clinically-viable platform-based vaccine strategy, termed the NanoLymph, to provide spatiotemporal elution of immunostimulants and tumor antigens locally to recruit and activate antitumor immunity for cancer eradication. Here, we aim to target the release of granulocyte macrophage colony stimulating factor (GM-CSF) and TLR-7/8 agonist Resiquimod (R848) to promote recruitment and activation of dendritic cells (DCs), a key player in antitumor cytotoxicity. Results: We demonstrate the NanoLymph as an structurally stable and biocompatible immunostimulatory niche for durable DC-driven tumor specific T-cell mediated cytotoxicity. Additionally, we demonstrate the NanoLymph's ability to recruit and activate immune cells of interest, activating antitumor immunity against model antigen. Thus, we have provided the framework necessary to develop a personalized therapeutic cancer vaccine for tumor-specific T-cell mediated responses necessary to generate immunological memory. Conclusions: Future studies will evaluate immunostimulant and tumor antigen biodistribution in vivo and further apply the NanoLymph in a tumor bearing model to effect antitumor cytotoxicity. Ultimately, we aim to develop a personalized platform applicable for every patient of any cancer type aimed at direct clinical translation. Ethics Approval: This study was approved by the Houston Methodist Research Institute (HMRI), according to protocols approved by the Institutional Animal Care and Use Committee (IACUC). HMRI's Animal Welfare Assurance number is A4555-01. HMRI assures strict compliance with all federal regulations and guidelines involving the use of laboratory animals in biomedical research.